How strict is galactose restriction in adults with galactosaemia?: international practice - Adam, Sarah; Sahm, Katja (Molecular genetics and metabolism, 2015)
Dietary management of 418 adult patients with galactosaemia (from 39 centres/12 countries) was compared. All centres advised lactose restriction, 6 restricted galactose from galactosides ± fruits and vegetables and 12 offal. 38% (n = 15) relaxed diet by: 1) allowing traces of lactose in manufactured foods (n = 13) or 2) giving fruits, vegetables and galactosides (n = 2). Only 15% (n = 6) calculated dietary galactose. 32% of patients were lost to dietetic follow-up. In adult galactosaemia, there is limited diet relaxation.
Gesehen am 24.08.2017